PENGARUH PENGGUNAAN MEDIA RAINBOW SALT TRAY TERHADAP KEMAMPUAN MENULIS HURUF PADA ANAK USIA 4-5 TAHUN DI PAUD TERPADU KASIH IBU KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Chindia Viona; Ria Novianti; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is aimed (1) to find out the writing letters ability of children age 4-5 years in PAUD Terpadu Kasih Ibu District Gunung Toar of Kuantan Singing before were given use rainbow salt tray media, (2) to find out the writing letters ability of children age 4-5 years in PAUD Terpadu Kasih Ibu District Gunung Toar of Kuantan Singing after were given use rainbow salt tray media,(3) to find out whether the rainbow salt tray media affected on the age 4-5 years in PAUD Terpadu Kasih Ibu District Gunung Toar of Kuantan Singing. The population in this study that children age 4-5 years totaling 15 children and sample in this study amounted to 15 children. The method used pre-experimental design with one group pretest posttest design that experiments conducted on one group alone with no comparison group. This type of instrument used in this study is to use the observation and documentation. So the result of this research were (1) the the writing letters ability of children age 4-5 years in PAUD Terpadu Kasih Ibu District Gunung Toar of Kuantan Singing before were given use rainbow salt tray media is in developing category, (2) the writing letters ability of children age 4-5 years in PAUD Terpadu Kasih Ibu District Gunung Toar of Kuantan Singing after were given use rainbow salt tray media is in developing category as expected, (3) there is a significant effect on the rainbow salt tray media to the writing letters ability of children age 4-5 years in PAUD Terpadu Kasih Ibu District Gunung Toar of Kuantan Singing. It is known that there is difference that an improving of writing letters ability to children before and after treatment. Rainbow salt tray media has an effect as 56,07% on the children age 4-5 years in PAUD Terpadu Kasih Ibu District Gunung Toar of Kuantan Singing.Keywords: Writing letters, Rainbow salt tray media